The Symbols of Inculturation and Interfaith in The Demak's Great Mosque - Awaliyah, Dian Nafiatul (Universitas Islam Negeri Sunan Kalijaga, 2024)
This research presents a reinterpretation of the Lawang Bledheg ornamentation found in the Great Mosque of Demak, Central Java, Indonesia. The study explores the profound connections between architectural ornamentation and the message conveyed in the referenced Quranic verses through an interdisciplinary approach combining aesthetic and symbolic analysis. By conducting on-site observations, examining historical records, and analyzing Islamic artistic conventions, the research unveils the symbolic meanings embedded within the Lawang Bledheg ornaments. The findings demonstrate that the ornaments represent a fusion of local Javanese artistic traditions and Islamic influences, creating a unique cultural synthesis. The research also highlights the symbolism of unity, tolerance, and religious harmony depicted through the motifs, patterns, and decorative elements of the Lawang Bledheg ornament. These symbols resonate with the themes present in Surah Ali Imran verses 133-136, emphasizing the inclusive nature of the Great Mosque of Demak as a sacred space. By shedding light on the aesthetic and symbolic aspects of the Lawang Bledheg ornamentation, this research contributes to a deeper understanding of the mosque's cultural significance, encourages interfaith dialogue, and inspires contemporary architectural designs. The findings enrich art history, architecture, and religious studies, offering valuable insights into the intricate relationship between art, spirituality, and cultural heritage.